TEACHERS’ PERSPECTIVES ON THE USE OF ARTIFICIAL INTELLIGENCE (AI) IN CLASSROOM LEARNING IN WEST ACEH - Puput Marlisa; Nursiah (Jurnal Bionatural, 2026)
This study aims to analyze the perceptions of teachers in West Aceh regarding the use of Artificial Intelligence (AI) in learning. Perceptions were measured through five key dimensions: (1) Perceived Usefulness, (2) Perceived Ease of Use, (3) Attitude towards AI, (4) Perceived Risk and Concern, and (5) Readiness and Behavioral Control. The research employed a descriptive quantitative approach with a survey method. The research sample consisted of 29 teachers from various educational levels in West Aceh, selected purposively. Data were collected using a closed-ended questionnaire with a Likert scale and analyzed using descriptive statistics. The results indicate that teachers' perceptions are overwhelmingly positive. The dimension of Readiness and Behavioral Control received the highest score (87.07%), followed by Perceived Usefulness (84.48%), Attitude towards AI (82.93%), and Perceived Ease of Use (82.76%), all of which are in the high category. Conversely, the Perceived Risk and Concern dimension recorded the lowest percentage (38.10%), indicating that teachers do not perceive AI as a significant threat or risk in educational practice. These findings depict a highly conducive environment for AI adoption, where teachers feel ready, see clear benefits, and have minimal concerns. Based on the findings, this study recommends enhancing practical competency-based training programs, establishing teacher learning communities, developing ethical guidelines, and strengthening school infrastructure to support sustainable and effective AI implementation.